HUBUNGAN POLA ASUH ORANG TUA DENGAN HASIL BELAJAR SISWA KELAS V SD NEGERI 101764 BANDAR KLIPPA - Desy Natalia Br Ginting; Reflina Sinaga; Heka Maya Sari Sembiring; Antonius Remigius Abi; Irmina Pinem (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The study aims to determine the relationship between parenting patterns and learing outcomes of class V SD Negeri 101764 Bandar Klippa Learning Year 2023/2024. The populations in this study was all calas V students at Bandar Klippa, totaling 112 students. The sampel used in this was random sampling type, in this case the researcher used the Solving Formula so that the total sampel in this study was 88 people consisting of 44 students from classes VA and VB and their parents. In this research, researchers used a quantitative survey type method. The methode used to test the hypotesis uses correlation techniques, the correlation  techique used is pearson product meoment correlation. The results of this study indicate taht there is a positive correlation parenting patterns with student learning outcomes. This is proven by the correlation value is 2.624 ≥ ttabel 1.680. it can be concluded that tcount ≥ t table is accepted that there ia a relationship between parental parenting patterns and learning outcomes of class V students at SD Negeri 101764 Bandar Klippa Learning Year 2023/2024.